(untitled) (A Text Book of Pharmaceutics for I Year Diploma in Pharmacy, 2024)
Author Mr. Sharib Jamal Associate Professor, Dept. of Pharmaceutics, Mesco Institute of Pharmacy, Amroha, Uttar Pradesh, India Abstract: Pharmaceutical manufacturing plants are complex facilities designed to produce high-quality medicinal products in compliance with regulatory standards. This section provides an overview of the key components and considerations in designing and operating a pharmaceutical manufacturing plant. The layout and design principles of manufacturing facilities, including material and personnel flow, are discussed with emphasis on contamination control and operational efficiency. Various production areas, such as dispensing, granulation, compression, and packaging, are explored along with their specific equipment requirements. The concept of current Good Manufacturing Practices (cGMP) and its implementation in facility design and operation is examined. Utility systems critical to pharmaceutical manufacturing, including HVAC, water purification, and compressed air systems, are addressed. Quality assurance and quality control functions within the manufacturing plant, including in-process controls and finished product testing, are detailed. Environmental monitoring programs and their role in maintaining product quality are discussed. The importance of documentation systems, including batch records and standard operating procedures, is highlighted. Facility validation processes, including equipment qualification and process validation, are explored. Keywords: cGMP compliance, Facility design, Contamination control, Utilities, Process validation, Quality systems View PDF